Transformasi Perguruan Tinggi Keagamaan Islam Negeri Langsa Pasca Konflik Aceh - Basri, Basri (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2023)
The purpose of this study is to analyze the transformation of IAIN Langsa over time. It also aims to see how the dynamics of the Langsa State Islamic institute changed during and after the conflict in Aceh. This type of library research is used in this study to examine important documents related to research issues. The historical approach in research examines the transformation journey of IAIN Langsa before and after the conflict that occurred in Aceh. The results showed that the conflict that occurred between the Aceh Independence Movement (GAM) and the Government of Indonesia greatly influenced the progress of IAIN Langsa; a significant influence was felt from the educational aspect, campus development. The conflict that occurred caused students to be less interested in continuing their education at the tertiary level. However, the occurrence of peace between GAM and the Government of Aceh also influenced the acceleration of education development. This condition also sparked IAIN Langsa, which was previously a State Islamic institute (IAIN) and has transformed into a state Islamic university (IAIN). This change has increasingly attracted the sympathy of students who want to continue their education at the tertiary level after the conflict. There are at least four achievements made by IAIN Langsa, namely: first, institutional legality increases; second, community satisfaction is getting higher; third, being able to respond to the development of science; And fourth, increasingly integrated science